Surgical strategy of laparoscopic partial nephrectomy: It is more suitable to use transperitoneal approach in anterior tumor patients and retroperitoneal approach in posterior tumor patients - Li, Yijian; Huang, Li; Liu, Wentao (Frontiers in Oncology, 2023)
Background: Previous surgical strategy of transperitoneal laparoscopic partial nephrectomy (TLPN) and retroperitoneal laparoscopic partial nephrectomy (RLPN) for treatment of renal cell carcinoma (RCC) mainly depend on surgeons’ preference. The aim of this study was to evaluate whether performing TLPN for anterior tumors and RLPN for posterior tumors is a more beneficial strategy. Methods：214 patients underwent TLPN or RLPN at our center were retrospectively collected and 1:1 matched for surgical approach, tumor complexity as well as operator. Baseline characteristics and perioperative outcomes were evaluated and compared, respectively. Results：Regardless of tumor location, RLPN was associated with a faster operative time, a quicker time to first oral intake and hospital discharge compared to TLPN approach while other baseline and perioperative outcomes were comparable between groups. After taking tumor location into consideration, TLPN has an advantage in operating time (109.8 vs 115.3 mins, p = 0.03) and ischemic time (20.3 vs 24.1 mins, p = 0.001) for anterior tumor, while RLPN has an advantage in operating time (103.5 vs 116.3 mins, p<0.001), ischemic time (21.8 vs 24.8 mins, p = 0.001) and estimated blood loss (65.5 vs 85.4 ml, p = 0.01) for posterior tumor. Conclusion：The selection of approach should be also dependent of the tumor location, instead of only dependent of surgeons’ experience or preference.